2016
DOI: 10.1016/j.scitotenv.2016.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and risk of respiratory and cardiovascular hospitalizations in the most populous city in Vietnam

Abstract: Air pollution has become an alarming issue in Vietnam recently; however, there was only one study so far on the effects of ambient air pollution on population health. Our study aimed to investigate the short-term effects of air pollutants including PM10, NO2, SO2, and O3 on respiratory and cardiovascular hospitalizations in Ho Chi Minh City (HCMC), the largest city in Vietnam. Data on hospitalization from the two largest hospitals in HCMC and daily records of PM10, NO2, SO2, O3 and meteorological data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(103 citation statements)
references
References 30 publications
7
94
2
Order By: Relevance
“…Also other studies from China such as, Zhang et al’s study from Beijing, [1], Tao et al’s study from Lanzhou [20], and Liu et al’s study from Jinan [22], reported that an increase of 10 μg/m 3 of SO 2 corresponded to a 35%, 0.5% and 1.2% increase of respiratory diseases hospitalizations, respectively. Another study done by Phung et al from Vietnam also found that SO 2 was positively associated with the number of respiratory hospital admissions [36]. The mean annual concentration of SO 2 in most of the mentioned studies that reported significant association between SO 2 levels and respiratory hospital admissions, were higher than the present study.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Also other studies from China such as, Zhang et al’s study from Beijing, [1], Tao et al’s study from Lanzhou [20], and Liu et al’s study from Jinan [22], reported that an increase of 10 μg/m 3 of SO 2 corresponded to a 35%, 0.5% and 1.2% increase of respiratory diseases hospitalizations, respectively. Another study done by Phung et al from Vietnam also found that SO 2 was positively associated with the number of respiratory hospital admissions [36]. The mean annual concentration of SO 2 in most of the mentioned studies that reported significant association between SO 2 levels and respiratory hospital admissions, were higher than the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…A study done by Wilson et al from Europe in 2005 reported that increases in O 3 , was not positively associated with the number of all respiratory hospitalizations in Portland and Manchester, UK [19]. Another study done by Phung et al investigated air pollution and the risk of respiratory and cardiovascular hospitalizations in Vietnam and did not show any significant association between O 3 and respiratory hospitalizations [36]. Also Fung et al study in 2005 in Ontario, Canada did not find any association between O 3 and respiratory diseases admissions either [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations